2019
DOI: 10.15763/issn.2376-5267.2018.1.5.122-147
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Significantly Predict Academic, Athletic Career Motivation among NCAA Division I College Athletes

Abstract: American society has had college athletics at its core for over a century (Rader, 2009) and is ubiquitous in University life.  College athletes’ performances both on and off the field have been scrutinized in both popular and academic literature.  Other examples include the documentation in student development literature that meaningful engagement outside traditional classroom settings can have positive effects on a student’s (athlete or not) personal development (Pascarella & Terenzini, 2005). College ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Previous research examining the relationship between athlete academic success and GPA found variations across sport type and season of competition (Dilley-Knoles et al, 2010). Female athletes were found to have higher grade point averages (LeCrom et al, 2009;Staurowsky et al, 2020), and a coach, athletic department, and institution emphasizing high academic importance influences college athlete academic success (Ridpath, 2002;Tudor & Ridpath, 2018). While the 2.0 standard is the minimum for athletic eligibility, communicating a higher target of 3.0 and connecting students to support services may facilitate more athlete academic success and increase retention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research examining the relationship between athlete academic success and GPA found variations across sport type and season of competition (Dilley-Knoles et al, 2010). Female athletes were found to have higher grade point averages (LeCrom et al, 2009;Staurowsky et al, 2020), and a coach, athletic department, and institution emphasizing high academic importance influences college athlete academic success (Ridpath, 2002;Tudor & Ridpath, 2018). While the 2.0 standard is the minimum for athletic eligibility, communicating a higher target of 3.0 and connecting students to support services may facilitate more athlete academic success and increase retention.…”
Section: Discussionmentioning
confidence: 99%
“…This prompted more researchers to study student-athlete motivation with both academic and athletic motivation in mind. Using the SAMSAQ, Tudor & Ridpath (2018) examined perceived motivational climate and motivation, discovering a task-involved climate in sports predicted both high sport motivation and high academic motivation. Continued application of the SAMSAQ with different constructs can contribute further to research on relationships connected to college student-athlete motivation.…”
Section: Student-athlete Learning and Motivationmentioning
confidence: 99%
“…Research likewise suggests that gender is a factor in academics among college students, with women more likely to commit more time in academic tasks than men (Hanson et al, 2011;Quadlin, 2016), and female student-athletes in particular are more academically motivated than their male counterparts (Tudor & Ridpath, 2019). The interaction of gender and race was also found to influence the student engagement of college students (Hu & Wolniak, 2013), while division level is assumed to impact time utilization in athletics (Comeaux et al 2011;Griffith & Johnson, 2002).…”
Section: Main Effects Of Gender Race and Division Levelmentioning
confidence: 99%